2017
DOI: 10.4103/1793-5482.185061
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the xenograft bone plate-screw system in lumbar transpedicular stabilization: An in vivo study in dogs

Abstract: Objectives:Xenograft bone plate-screws (XBPSs) can be alternative tools in lumbar transpedicular stabilization (TS). The aim of this study was to show biomechanical and histopathological contribution of the XBPSs system in lumbar TS.Materials and Methods:Fifteen (n = 15) hybrid dog and ten (n = 10) L2-4 cadaveric specimens were included in the study. The dogs were separated according to surgical techniques: L3 laminectomy and bilateral facetectomy (LBF) in Group I (experimental group [EG I] (n = 5), L3 LBF plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…In radiological follow-ups of the experimental group, it was observed that resorption developed from the 1 st month on the intervertebral XG and XGVPs and fusion development had radiologically occurred at the end of the 3 rd month. Vascularization increase, fibrosis, ossification and development of cartilaginous islets were observed in the fusion area in the subjects of the experimental group (24).…”
Section: Results Of the Biomechanical Studiesmentioning
confidence: 91%
See 1 more Smart Citation
“…In radiological follow-ups of the experimental group, it was observed that resorption developed from the 1 st month on the intervertebral XG and XGVPs and fusion development had radiologically occurred at the end of the 3 rd month. Vascularization increase, fibrosis, ossification and development of cartilaginous islets were observed in the fusion area in the subjects of the experimental group (24).…”
Section: Results Of the Biomechanical Studiesmentioning
confidence: 91%
“…Although there is plenty of information about obtaining fusion by using autograft, allograft, and synthetic and osteoinductive factors (8)(9)(10)13,15,18,31,37), there is only one elucidative experimental study about the use of xenografts (24). Furthermore, there is currently no study on obtaining fusion through a stabilization system with plate and screws prepared from a xenograft (XG) for anterior lumbar vertebrae.…”
mentioning
confidence: 99%